Effective Implementation of ICT for rural development: Opportunities and Challenges - Havinal, Ramanna (International Journal of Computer Sciences and Engineering, 2020)
Information and communication technology (ICT) play a key role in rural development and the economy of a country. The present rural development strategy mainly focuses on poverty alleviation, better livelihood, provision of basic amenities and infrastructure facilities.. Usage of ICT in rural area, not only speed up the development process but also reduce the gaps between urban and rural sectors of the society. The ICT applications have lot of opportunities for rural development and will also have some challenges. It can be used to distribute its services to all - citizens, businesses, and government. ICT is changing at a rapid speed but its application in rural area is very progressing slowly, because of lack of literacy and resources. It is necessary to focus on the scope of ICT in rural development, the opportunities and the challenges [1].Major problems in rural areas are electricity, communication, transportation and lack of knowledge about new technology [2]. This paper is to focus on reviewing and analyzing interpreting existing ideas of the researchers and to explain the role of information communication technology in the rural development and to show how ICT approaches will be effective in helping the rural people for their sustainable developmen.